Renewable energy and power supply challenges for rural regions/ Valeriy Kharchenko and Pandian Vasant, editors. - Kharchenko Valeriy; Vasant Pandian (2019)
Includes bibliographical references and index. "This book examines theoretical and experimental research in the field of renewable energy sources. It explores the application of electrical technologies in agro-engineering processes that provide increased yields, increased productivity, and improved working conditions. It also highlights the issues of the energy supply of agricultural production and the household aspects of life in rural areas"-- Chapter 1. Solar concentrators: solar modules based on holographic films -- Chapter 2. Tools and methods of information support for the development of renewable energy -- Chapter 3. Electrical and heat power production using the products of air conversion of motor diesel fuel and electrochemical generator for agricultural consumers -- Chapter 4. Increasing the energy efficiency of photovoltaic systems operating under conditions of uneven illumination -- Chapter 5. Materials and methods of thermal energy storage in power supply systems -- Chapter 6. Creating a synergy: renewable energy to develop the Russian Arctic -- Chapter 7. Renewable energy sources development in rural areas of African countries -- Chapter 8. Designing solar power plant due to consumer load schedule, solar energy potential, and electricity prime cost -- Chapter 9. The exploitation of wind systems in rural electrical network -- Chapter 10. Factors affecting the power-efficient operation of wind-diesel complexes -- Chapter 11. Strategies for protection systems of wind turbines with doubly fed induction generator: control strategies and techniques for fault ride through of doubly fed induction wind generator -- Chapter 12. Energy and water saving on the pumping stations of karshi main canal -- Chapter 13. Improving the power quality of rural consumers by means of electricity cost adjustment -- Chapter 14. Resonant power system for electric transport -- Chapter 15. Methods of reducing the power supply outage time of rural consumers. 1 online resource (25 PDFs (432 pages))